Structured Reporting of Medical Findings: Evaluation of a System in Gastroenterology - Kuhn, K.; Gaus, W.; Wechsler, J. G.; Janowitz, P.; Tudyka, J.; Kratzer, W.; Swobodnik, W.; Ditschuneit, H. (Methods of Information in Medicine, 1992)
A system using structured reporting of findings was developed for the preparation of medical reports and for clinical documentation purposes in upper abdominal sonography, and evaluated in the course of routine use. The evaluation focussed on the following parameters: completeness and correctness of the entered data, the proportion of free text, the validity and objectivity of the documentation, user acceptance, and time required. The completeness in the case of two clinically relevant parameters could be compared with an already existing database containing freely dictated reports. The results confirmed the hypothesis that, for the description of results of a technical examination, structured data reporting is a viable alternative to free-text dictation. For the application evaluated, there is even evidence of the superiority of a structured approach. The system can be put to use in related areas of application.
Keywords: Documentation System; Evaluation; Structured Data